Saraguro-Yacuambi-Loja Rural development Project: Ecuador: project brief (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
This document is a summary of the Saraguro-Yacuambi-Loja Rural Development Project in Ecuador, which covers general information and description of the project, agriculture and rural poverty, IFAD activities in Ecuador, geography and marketing and the dissemination of the project and its benefits.